Assessment of the relationship between gut microbiota, inflammatory markers, and colorectal cancer - Cui, Yan (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study aims to evaluate the correlation between inflammation and gut microbiota characteristics in patients with colorectal cancer (CRC) through a retrospective study.MethodsThis cross-sectional, non-interventional study included a total of 200 subjects, of which 150 were colorectal cancer (CRC) patients and 50 were healthy individuals. The study retrospectively reviewed hospital and laboratory archives and records from 2015 to 2020. Gut microbiota was analyzed using 16S rRNA sequencing. Inflammatory markers, including C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and interleukin-beta (IL-1β), were measured using enzyme-linked immunosorbent assay (ELISA). Logistic regression analysis was used to evaluate the relationship between gut microbiota, inflammatory markers, and CRC.ResultsSubjects in the colorectal cancer (CRC) group exhibited a higher proportion of Firmicutes (47.2% vs. 39.0%). Levels of both Firmicutes and Proteobacteria were significantly elevated in the CRC group, while Bacteroidetes levels were lower. Additionally, elevated levels of inflammatory markers were observed in the CRC group, including C-reactive protein (CRP: 9.8 mg/L vs. 4.1 mg/L, P<0.01), interleukin-6 (IL-6: 14.5 pg/mL vs. 6.2 pg/mL, P<0.01), tumor necrosis factor-alpha (TNF-α: 9.2 pg/mL vs. 4.3 pg/mL, P<0.01), and interleukin-1β (IL-1β: 5.8 pg/mL vs. 3.6 pg/mL, P<0.01). Multivariate analysis showed that higher levels of Firmicutes (OR=2.5, 95% CI: 1.4-4.5, P<0.01) and Proteobacteria (OR=2.8, 95% CI: 1.6-4.9, P<0.01) were significantly associated with an increased risk of CRC. Elevated levels of CRP (OR=3.1, 95% CI: 1.8-5.3, P<0.01) and IL-6 (OR=3.4, 95% CI: 2.0-5.8, P<0.01) were also significantly associated with an increased risk of CRC.ConclusionThere is a significant correlation between changes in gut microbiota composition and cytokine levels with the risk of colorectal cancer (CRC).